2016
DOI: 10.1016/j.taap.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n-3 PUFAs augment caspase 8 activation in Staphylococcal aureus enterotoxin B stimulated T-cells

Abstract: Epidemiological studies have linked consumption of n-3 PUFAs with a variety of beneficial health benefits, particularly with respect to putative anti-inflammatory effects. Unfortunately, many of these results remain somewhat controversial because in most instances there has not been a linkage to specific molecular mechanisms. For instance, dietary exposure to low levels of mercury has been shown to be damaging to neural development, but concomitant ingestion of n-3 PUFAs as occurs during consumption of fish, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In the preceding section, we have reminded the role of Hg as an autoimmunity trigger ( 17 , 44 51 ). However, omega-3 PUFA antagonize this effect of Hg ( 128 , 129 ). Gill et al.…”
Section: Fish and Omega-3 Pufa As Protection From Thyroid Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the preceding section, we have reminded the role of Hg as an autoimmunity trigger ( 17 , 44 51 ). However, omega-3 PUFA antagonize this effect of Hg ( 128 , 129 ). Gill et al.…”
Section: Fish and Omega-3 Pufa As Protection From Thyroid Disordersmentioning
confidence: 99%
“…Gill et al. ( 129 ) showed that dietary ingestion of n-3 PUFA (fish oil) promotes CD95 signaling by upregulating caspase 8 activation and that DHA counteracts the negative effect of Hg on CD95 signaling in T lymphocytes ( 128 ).…”
Section: Fish and Omega-3 Pufa As Protection From Thyroid Disordersmentioning
confidence: 99%